Improvement in Midline Shift Is a Positive Prognostic Predictor for Malignant Middle Cerebral Artery Infarction Patients Undergoing Decompressive Craniectomy - Chen, Xin; Hao, Qiang; Yang, Shu-Zhe; Wang, Shuo; Zhao, Yuan-Li; Zhang, Dong; Ye, Xun; Wang, Hao (Frontiers in Neurology, 2021)
Objective：The aim of this retrospective study is to evaluate the risk factors of Malignant Middle Cerebral Artery Infarction (MMCAI) patients and explore an applicable prognostic predictor for patients of Malignant Middle Cerebral Artery Infarction (MMCAI) patients undergoing Decompressive Craniectomy (DC). Methods：Clinical Data from the period 2012-2017 were retrospectively evaluated. 43 consecutive patients MMCAI patients undergoing DC were enrolled in this study. The 30-day mortality was assessed, and age, location, hypertension, pupil dilation, onset to operation duration, midline shift and GCS score were identified by univariate analysis and binary logistic regression. Results：In this retrospective study for the DC patients, the 30-day mortality is 44.2%. In the univariate analysis, Advanced age (≥60), right hemispheric location, hypertension, pupil dilation, shorter onset to operation duration (<48h), improved midline shift (t=4.214, P<0.01), and lower pre-operation GCS score are significant predictors of death within 30 days. In Binary logistic regression analysis, age (OR=1.141, 95%CI 1.011-1.287), the improvement of the midline shift (OR=0.764, 95%CI 0.59-0.988), and pupillary dilation (OR=15.10, 95%CI 1.374-165.954) are independent influencing factors. For the ROC analysis of the relationship between post-operation outcomes and midline shift improvement, the AUC is 0.844, and the cutoff point of midline shift improvement is 0.83 cm. Conclusion: Improved midline shift is a significant predictor of 30-day mortality. The improved midline shift of >0.83cm indicates survival at 30 day.